Efektivitas Bagian Laba atas Penyertaan Modal pada BUMD terhadap Pendapatan Asli Daerah Provinsi Jawa Timur - Dinda Aulia Damayanti; Rida Perwita Sari (Yayasan Education and Social Center, 2023)
This study evaluates the impact of regionally owned enterprises' equity participation share on original regional revenue in the East Java Province. The Regional Financial and Asset Management Agency of East Java Province provided the Budget Realization Report from 2017 to 2021, which is the source of the data. This study employs quantitative and descriptive analysis techniques and a WarpPLS 7.0 research test instrument. The results of this study suggest that the original regional revenue is influenced by the effectiveness of the profit share on the submission of capital to regionally owned enterprises. The degree of effectiveness ratio hits an average of 100.71 per cent from 2017 to 2021 and is classified as very effective